THE ATTRIBUTES OF PERSONAL TAXPAYER’S COMPLIANCE IN INDONESIA - Syafriel, Mohammad (ACCOUNTABILITY, 2018)
The aim of this study is to confirm the attributes of personal taxpayer’s compliance in Indonesia. The attributes of personal taxpayer’s compliance proposed in this research are: awareness, knowledge, perceived equality and fairness, compliance cost, fiscal service quality, tax socialization, tax regulation, tax audit and penalties. The data was gathered from 350 personal taxpayers registered in tax offices of several provinces of Indonesia. The data was processed using Second Order Confirmatory Factor Analysis (SEM-PLS) – SmartPLS 3. The result of the study confirmed that the attributes of awareness, positively, manifest the taxpayer’s compliance. It is also confirmed that the attributes of knowledge, positively, manifest the taxpayer’s compliance. The attributes of compliance cost, positively, manifest the taxpayer’s compliance. The attributes of perceived equality and fairness, positively, manifest the taxpayer’s compliance. The attributes of fiscal quality service, positively, manifest the taxpayer’s compliance. The attributes of tax socialization, positively, manifest the taxpayer’s compliance. The attributes of tax regulation, positively, manifest the taxpayer’s compliance. The attributes of tax audit, positively, manifest the taxpayer’s compliance. The attributes of penalties, positively, manifest the taxpayer’s compliance. These can be concluded that all of the attributes of the constructs confirm to indicate or manifest the personal taxpayer’s compliance in Indonesia.